Poročilo o obročkanju ptic v Sloveniji v letu 2017 in kratek pregled barvnega obročkanja v obdobju 2012-2017 - Vrezec, Al; Fekonja, Dare (Acrocephalus, 2022)
In 2017, the Slovenian bird ringing scheme concluded 90 years of continuous ringing in the country. In 2017, we collected data on 176 bird species. We ringed 79,886 birds of 164 species, recorded 177 recoveries of birds ringed in Slovenia and found abroad, 295 foreign recoveries in Slovenia and 2,209 local recoveries. The most ringed species were the Blackcap Sylvia atricapilla and Great Tit Parus major and, among pulli in the nest, the Great Tit, White Stork Ciconia ciconia and Barn Swallow Hirundo rustica. In 2017, 12 colour ringing schemes were active in Slovenia. In the 2012-2017 period, the number of recoveries of birds ringed in Slovenia and found abroad increased significantly due to colour ringing, especially regarding the waterbirds. With colour ringing, the likelihood of recoveries is considerably greater (75.20 ± 91.36 recoveries per 100 ringed birds) than with metal ringing only (0.11 ± 0.08 recoveries per 100 ringed birds). Among local recoveries, the most frequent were the Mute Swans Cygnus olor and Common Terns Sterna hirundo, and among foreign recoveries the Black-headed Gulls Chroicocephalus ridibundus predominated. In 2017, the first Broad-billed Sandpiper Calidris falcinellus was ringed in Slovenia (Sečovlje salinas), and additional three rare species were ringed as well: the Yellow-browed Warbler Phylloscopus inornatus (Ljubljansko barje), Paddyfield Warbler Acrocephalus agricola (Ljubljansko barje) and Little Bunting Emberiza pusilla (Šentrupert)